AIEgen-self-assembled nanoparticles with anti-PD-L1 antibody functionalization realize enhanced synergistic photodynamic therapy and immunotherapy against malignant melanoma - Lu Li; Qing Xu; Xiuzhen Zhang; Yuan Jiang; La Zhang; Jiao Guo; Haichuan Liu; Bin Jiang; Shenglong Li; Qiling Peng; Ning Jiang; Jianwei Wang (Materials Today Bio)
Immune checkpoint inhibitors (ICIs) become integral in clinical practice, yet their application in cancer therapy is constrained by low overall response rates and the primary resistance of cancers to ICIs. Herein, this study proposes aggregation-induced emission (AIE)-based nanoparticles (NPs) for a more effective and synergistic approach combining immunotherapy and photodynamic therapy (PDT) to achieve higher responses than anti-PD-L1 monotherapy. The TBP@aPD-L1 NPs are constructed by functionalizing azide group-modified TBP-2 (TBP-N3) with anti-PD-L1 antibodies via the DBCO-S-S-PEG2000-COOH linker. The anti-PD-L1 target the tumor cells and promote the TBP-N3 accumulation in tumors for enhanced PDT. Notably, the TBP-N3, featuring aggregation-induced emission, boosts reactive oxygen species (ROS) generation through both type I and type II processes for enhanced PDT. The TBP@aPD-L1-mediated PDT induces more powerful effects of direct tumor cell-killing and further elicits effective immunogenic cell death (ICD), which exerts anti-tumor immunity by activating T cells for ICI treatment and reshapes the tumor immune microenvironment (TIME), thereby enhancing the efficacy of PD-L1 blockade of anti-PD-L1. Consequently, TBP@aPD-L1 NPs demonstrated significantly enhanced inhibition of tumor growth in the mouse model of malignant melanoma (MM). Our NPs act as a facile and effective drug delivery platform for enhanced immunotherapy combined with enhanced PDT in treating MM.